2022
DOI: 10.1038/s41467-022-33169-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an inactivated Covid-19 vaccine with homologous and heterologous boosters against Omicron in Brazil

Abstract: The effectiveness of inactivated vaccines (VE) against symptomatic and severe COVID-19 caused by omicron is unknown. We conducted a nationwide, test-negative, case-control study to estimate VE for homologous and heterologous (BNT162b2) booster doses in adults who received two doses of CoronaVac in Brazil in the Omicron context. Analyzing 1,386,544 matched-pairs, VE against symptomatic disease was 8.6% (95% CI, 5.6–11.5) and 56.8% (95% CI, 56.3–57.3) in the period 8–59 days after receiving a homologous and hete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 36 publications
12
56
0
Order By: Relevance
“…We found that the protection against severe COVID-19 was highest with boosters received >14 days to 2 months prior to positive test (93%) and persisted between 2-4 months (91%) but started to wane between 5-6 months (77%) and further beyond 6 th month (68%). Our results are consistent with ndings from the US [16], Brazil [17] and Finland [18], where effectiveness of booster vaccines against COVID-19associated severe outcomes started to decline after 4 months.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the protection against severe COVID-19 was highest with boosters received >14 days to 2 months prior to positive test (93%) and persisted between 2-4 months (91%) but started to wane between 5-6 months (77%) and further beyond 6 th month (68%). Our results are consistent with ndings from the US [16], Brazil [17] and Finland [18], where effectiveness of booster vaccines against COVID-19associated severe outcomes started to decline after 4 months.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were seen in Brazil, where protection waned after 3-4 months from last booster vaccine, and the decline was more rapid with homologous schedules as compared to heterologous schedules [17]. Previous studies examined waning of booster vaccine effectiveness against severe outcomes in populations with predominantly homologous schedules [15,16,18] and only a handful of studies have examined heterologous schedules [17,19,20].…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Between 0–13 days and >180 days, the odds in 18–39-year-olds were 1.41 to 1.67, but they were 1.22 to 1.65 in those > 80 years old. In a study of the effectiveness of heterologous vs. homologous booster regimens, a homologous inactivated virus vaccine booster only resulted in a vaccine effectiveness of 15.0% against symptomatic COVID-19 8–59 days post-vaccination compared with 56.8% when given an mRNA vaccine booster, with higher vaccine effectiveness against hospitalization and death ≥ 60 days after the booster in heterologous vaccinees (78.5% vs. 51.4%) [ 20 ]. In combination, these studies seem to indicate that the declining antibody responses in inactivated virus vaccinees are associated with a decline in vaccine efficacy over time.…”
Section: Discussionmentioning
confidence: 99%